Water Quality Index (Ammoniacal Nitrogen, Biochemical Oxygen Demand, Chemical Oxygen Demand) Assessment In Sungai Kereh - Maenah, Mud (Universiti Sains Malaysia, 2022)
In the Malaysian state of Pulau Pinang, a river known as Sungai Kereh is significantly deteriorating due to the pollution caused by livestock farming, specifically pig farming. A study is conducted along the river to determine the water quality in Sungai Kereh during dry and wet seasons based on water quality parameters Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), pH, Suspended Solids (SS) and Ammoniacal Nitrogen (AN) to classify the river based on water quality index (WQI) from the Department of Environment (DOE). The objectives of this study are to assess the current water quality of Sungai Kereh using the WQI and to determine the relationship between the concentration of ammoniacal nitrogen (AN) with biochemical oxygen demand (BOD) and chemical oxygen demand (COD). It was discovered that the water quality deteriorates more during the dry season than during the wet season for most of the water quality parameters. During both seasons (dry and wet seasons), Sungai Kereh can be classified as Class V upstream of Parit Cina and consequently improves to Class IV, reaching downstream of Sungai Kereh. The leading cause of pollution in Sungai Kereh is due to the high concentration of ammoniacal nitrogen (AN). Pig farms are the primary source of pollution and water quality deterioration in this area. The high concentration of AN significantly affects BOD and COD concentration in the river compared to other parameters such as DO, pH and SS.